Physico-chemical and rheological indicators of meat pates with corn starch suspensions prepared with electrochemically activated water - Marynin, Andriy; Shpak, Vladyslav; Pasichnyi, Vladyslav; Sviatnenko, Roman; Shubina, Yevgenia (My University, 2023)
The aim of the study was to determine the influence of electrochemically activated water application on the rheological properties of corn starch suspensions and pates prepared with them. Corn starch suspensions were prepared on artesian water, which was activated by electrochemical treatment on a diaphragm electrolyzer. Physico-chemical characteristics of electrochemically activated water were determined using a Palintest 7500 photometer. Morphological studies of starch granules were carried out by scanning electron microscopy, and granulometric composition was determined by laser diffraction method. The rheological indicatorss of starch suspensions and pates were studied using a Kinexus Pro+ rheometer. The physico-chemical characteristics of electrochemically activated water except pH met the requirements of the European Parliament and Council Directive on the quality of water intended for human consumption. The water absorption capacity of starch when preparing its suspensions on a catholyte (obtained by passing a direct electric current through water in the cathode chamber of an electrolyzer) decreased by 26%, and when prepared on an anolyte (obtained in the process of water oxidation reactions on the anode) increased by 18%. The moisture holding capacity of hydrated starch decreased by 10% when using catholyte, and increased by 36% when using anolyte. Electrochemically activated water had a significant effect on the rheological characteristics of starch suspensions: with an increase in the percentage of complex shear strain, the shear stress increased proportionally for samples of suspensions made on electrochemically activated water. The viscoelastic properties of starch suspensions prepared using electrochemically activated water both at 25 ℃ and at 68 ℃ tended towards an ideally elastic gel, that is, they had more elastic structure than the control samples. Under the action of shear deformation, the elastic properties were lost, while the suspensions acquired viscosity (phase angle values increased). The maximum value of the moisture binding capacity of pates was observed when using a starch suspension prepared on anolyte. The best values of rheological characteristics of pates were obtained when using starch suspension with 2% starch prepared on anolyte. Electrochemically activated water had a significant effect on the physicochemical and rheological properties of semi-finished products, in particular corn starch suspensions, and pates prepared with them, and contributed to better structuring of the studied food systems.

Мета дослідження – визначити вплив застосування електрохімічно активованої води на реологічні властивості суспензій кукурудзяного крохмалю та паштетів, приготовлених з них. Суспензії кукурудзяного крохмалю готували на артезіанській воді, яку активували електрохімічною обробкою на діафрагмовому електролізері. Фізико-хімічні характеристики електрохімічно активованої води визначали за допомогою фотометра Palintest 7500. Морфологічні дослідження гранул крохмалю проводили методом скануючої електронної мікроскопії, а гранулометричний склад визначали методом лазерної дифракції. Реологічні показники крохмальних суспензій і паштетів досліджували за допомогою реометра Kinexus Pro+. Фізико-хімічні характеристики електрохімічно активованої води, крім pH, відповідали вимогам Директиви Європейського Парламенту та Ради щодо якості води, призначеної для споживання людиною. Водопоглинаюча здатність крохмалю при приготуванні його суспензії на католіті (отриманому пропусканням постійного електричного струму через воду в катодній камері електролізера) знизилася на 26%, а при приготуванні на аноліті (отриманому в процесі окислення води реакції на аноді) зросла на 18%. Вологоутримуюча здатність гідратованого крохмалю при застосуванні католіту знижується на 10%, а при використанні аноліту підвищується на 36%. Електрохімічно активована вода суттєво впливала на реологічні характеристики крохмальних суспензій: зі збільшенням відсотка комплексної деформації зсуву пропорційно зростала напруга зсуву для зразків суспензій, виготовлених на електрохімічно активованій воді. В’язкопружні властивості суспензій крохмалю, приготованих з використанням електрохімічно активованої води, як при 25 ℃, так і при 68 ℃ мали тенденцію до ідеально еластичного гелю, тобто вони мали більш еластичну структуру, ніж контрольні зразки. Під дією зсувної деформації втрачалися пружні властивості, а суспензії набували в’язкості (збільшувалися значення фазового кута). Максимальне значення вологозв'язувальної здатності паштетів спостерігалося при використанні суспензії крохмалю, приготовленої на аноліті. Найкращі значення реологічних характеристик паштетів отримано при використанні крохмальної суспензії з 2 % крохмалю, приготовленої на аноліті. Електрохімічно активована вода суттєво впливала на фізико-хімічні та реологічні властивості напівфабрикатів, зокрема суспензій кукурудзяного крохмалю, та паштетів, приготовлених з ними, та сприяла кращому структуруванню досліджуваних харчових систем.
Keywords: starch; meat pate; rheology; viscosity; electrochemically аctivated water; кафедра технології м’яса і м’ясних продуктів; кафедра електропостачання і енергоменеджменту; крохмаль; м'ясний паштет; реології; в'язкість; електрохімічно активована вода